Strategi Guru dalam Meningkatkan Kemampuan Hafalan Siswa di Kelas IV MI Darrussalamah Sumbersari - abdurrohman; Mustajib (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
An Islamic educational institution, especially pondok pesantren must not be separated from the yellow book and its teaching methods, a santri if they want to understand a book they must learn the science of tools (nahwu, shorof and balaghoh) therefore the need for a special learning method for the purpose of learning to succeed, on this occasion we are interested to discuss understanding the science of tools that focus on memorization strategies, of course in increasing the volume of memorization , and a quick trick in memorizing. Memorizing a book or nadhom is an activity that requires special intentions and strategies, especially for students at an early age who need guidance and direction from the teacher, in this context the researchers want to know how the teacher's strategy in guiding and directing his students to be passionate in memorizing the book and nadhom, on this occasion we as researchers had the opportunity to create an article that more or less discussed 1. About understanding teachers, 2. Learning strategies, 3. Methods, principles and factors of memorization.